The gift of family - Monroe, Mary (Dafina Books/Kensington Publishing Corp., 2020)
A middle-aged couple who have never been able to have children and an elderly widow who maintains a grueling schedule to support her grandkids come up with a solution to help both families during the holiday season, with unexpected results.